ChemInform Abstract: Application of the Dimensional Reduction Formalism to Pb12 [Li2(P2O7)2 (P4O13)2](P4O13): A Phosphate Containing Three Types of Isolated P—O Groups. Issue 41 (September 2016) - Zhang, Xiangyu; Wu, Hongping; Wang, Ying; Dong, Xiaoyu; Han, Shujuan; Pan, Shilie
Abstract: Polycrystalline Pb12 [Li2 (P2 O7 )2 (P4 O13 )2 ](P4 O13 ) is prepared via calcination of stoichiometric amounts of Li2 CO3, PbO, and NH4 H2 PO4 (Al2 O3 crucible, 630 °C, 3 d).